Ethno-medicinal Plants Used to Treat Gynaecological Disorders by Tribal Peoples of Paschim Medinipur District, West Bengal, India - Pandit, P. K.; Bhakat, R. K. (Indian Forester, 2009)
Ethno-medicinal plants are traditionally used by local tribal people of Paschim Medinipur District (West Bengal) since long for their healthcare. As many as 90 ethno-medicinal plant species have been identified which were traditionally used to cure gynaecological disorders like leucorrhoea, menorrhagia, amenorrhoea, dysmenorrhoea, etc. These were also used to treat related ailments and problem like birth control, contraception, gonorrhoea, spermatorrhoea, syphilis, regulation of menses and act as an aphrodisiac.